Environmental Sustainability and Corporate Responsibility: A Legal Framework for Indonesian Business in the Future - Arifudin, Nur; Purwanti, Purwanti (Faculty of Law, Universitas Pekalongan, 2024)
This study examines how legal frameworks, corporate responsibility, and environmental sustainability interact with one another in the Indonesian industry. The study evaluates business behavior, legal frameworks, and environmental governance through a normative analysis to find ways to improve sustainability and responsibility. The results highlight the positive aspects of Indonesia's legal system, including its extensive legislation and corporate responsibility-promoting programs. Nonetheless, there are still issues, such as lax regulations and ineffective enforcement systems. Stakeholder viewpoints highlight how crucial it is to promote sustainability through openness, public involvement, and multi-stakeholder cooperation. The suggestions include bolstering capacity-building initiatives, encouraging transparency, aligning regulations, enforcing stricter enforcement, and rewarding sustainable behaviors. By implementing these ideas, Indonesia may establish a more sustainable and conscientious corporate environment, striking a balance between environmental stewardship and economic growth.